Caso de estudio: análisis y diagnóstico de una empresa del sector agroindustrial peruano, propuesta de un plan estratégico - Gonzales Vega, Stefany Maria Esther (2019)
Camposol is an agro-industrial company dedicated to the cultivation of fruits, vegetables and marine products and the sale of them in the national and international market, for which it has offices in 4 different countries of the world. It is a vertically integrated company, which gives it greater control over the entire value-chain and generates an important competitive advantage over its competitors. For the development of Camposol's activities, favorable aspects are presented in the internal environment, such as the different quality certifications of its products and its friendliness with the environment, and in the external environment such as the free trade agreement in force with the United States and the opening of the Chinese market, in addition to the popularization of "superfoods"; and unfavorable as the high cost of payroll maintenance and the impact of the political crisis in the Peruvian market.